Anthropology of Food / The Social Dynamics of Food Security - Pottier Johan (Policy Press, 2007)
An impressive survey and discussion of recent anthropological research on the lack of fit between the lived realities of those who suffer food shortages and the perceptions of interested policy makers. In Search of Relevance, Food Security in Polity and Practice, Land and Livelihood, Labor Organization on Smallholder Farms, Playing the Food Market, The Politics of Identity, Famine Relief and Famine Prevention, Attractive Simplicity, State of Play, Index.